2022
DOI: 10.3389/fpsyg.2022.822788
|View full text |Cite
|
Sign up to set email alerts
|

More Lies Lead to More Memory Impairments in Daily Life

Abstract: Previous studies have demonstrated that lying can undermine memory and that its memory-undermining effects could be modulated by the cognitive resources required to tell lies. We extended the investigation of the memory-undermining effect by using a daily life setting in which participants were highly involved in a mock shopping task. Participants were randomly assigned to truth-telling, denying or mixed lying conditions. After finishing the shopping task, participants were told that two people wanted to know … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 52 publications
(135 reference statements)
3
6
0
Order By: Relevance
“…As indicated in the results section, the results achieved on the final memory test did not consider items erroneously replied to during the interview. We found that lying undermined both source and destination memory, which is consistent with previous studies (Li et al, 2022a , 2022b ; Li & Liu, 2021 ). Moreover, we did not observe any significant differences between the internally and externally motivated lying groups.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…As indicated in the results section, the results achieved on the final memory test did not consider items erroneously replied to during the interview. We found that lying undermined both source and destination memory, which is consistent with previous studies (Li et al, 2022a , 2022b ; Li & Liu, 2021 ). Moreover, we did not observe any significant differences between the internally and externally motivated lying groups.…”
Section: Discussionsupporting
confidence: 92%
“…Following previous studies (Li et al, 2022a , 2022b ; Li & Liu, 2021 ), all data were analyzed in the R system with the lme 4 package. A linear mixed‐effects (LMEs) model was used to analyze the belief and memory ratings, and a generalized linear mixed‐effects (GLMEs) model was used to analyze error rates, with participants and items serving as crossed random effects (Baayen et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations